Slope Stability of an Earth Dam during Drawdown Conditions (KHASA-CHAI Dam) as a Case Study - Jayed Zedan, Adnan; Ridha Faris, Mariwan; Amer Abdulsattar, Ahmed (International Journal of Engineering and Technology, 2018)
Aiming in this research was to have a clear view about the behavior of Khasa-Chai Dam during the draw down action taking into consideration the newly built of this dam which was filling during the time of this article, the upstream slope was investigated by taking drawdown of the water from the reservoir. This dam is consists of the zoned embankment with a total length of (2.36 km) with an upstream slope (1v:3h) and downstream slope (1v:2h). Slope stability was investigated during the drawdown of the water from the reservoir by considering the water in the reservoir to be at maximum water level and by taking two cases during the rapid and slow drawdown. SLOPE/W which is a sub program from Geo-Slope software was used in association with SEEP/W software to find the factor of safety of the upstream slip surface during the drawdown conditions. It was noticed from the drawdown conditions that the phreatic line falls almost at the same position for both cases. Also for both cases the factor of safety of the upstream slip surface falls above the value of (1.0) and that is mean the upstream slope is in a safe condition when the water drawdown. The exit gradient and the rate of flow at the downstream face decrease with time as the water in the reservoir drawdown which means the factor of safety against boiling increases with time.Â Â